Overcoming Criminal Acts of Corruption Outside the Court by Penal Means Based on Justice Based on the Principle of Efficiency - Mochamad Jeffry; Febrian; Nashriana; Ruben Achmad (PT. Global Research Collaboration, 2026)
Corruption remains a chronic problem in Indonesia, causing substantial state financial losses and hindering national development. Law No. 31 of 1999 as amended by Law No. 20 of 2001 prioritizes criminal sanctions, reflecting a retributive purpose of punishment where imprisonment is imposed regardless of the magnitude of state losses. This approach often proves inefficient, as handling costs may exceed recovered losses. This research examines three issues: (1) the regulation of corruption crimes using penal means based on the purpose of punishment; (2) the countermeasures of corruption using penal means based on the purpose of punishment; and (3) the countermeasures of fair corruption out of court using penal means based on the efficiency principle. Using normative legal research with statutory, conceptual, comparative, philosophical, and futuristic approaches, this study finds that the current retributive orientation contradicts the Corruption Law's goal of recovering state losses to achieve a just and prosperous society. In practice, law enforcement continues to prioritize imprisonment even in small-loss cases. This research proposes reformulating Article 4 of the Corruption Law to allow the return of state losses to eliminate punishment when loss values fall below enforcement budget thresholds, accompanied by a fine of one times the loss amount. This efficiency-based approach aligns with utilitarian theory and the fifth principle of Pancasila (social justice for all Indonesian people), ensuring that small-scale corruptors need not undergo imprisonment while prioritizing state financial recovery.